Memória institucional e bibliotecas universitárias: as Bibliotecas da ESPM como lugares de memória - Silva, Edson Sousa da (2024)
This dissertation investigates the relationship between institutional memory and university libraries, focusing on the libraries of the Escola Superior de Propaganda e Marketing (ESPM). Using Pierre Nora's theory of "places of memory", the research analyzes how these libraries contribute to the preservation and transmission of institutional memory. The methodology involves a bibliographical survey and a documentary analysis, with a qualitative approach. The results show that ESPM libraries play an essential role in the preservation of institutional memory, organizing and making available collections that record the trajectory and intellectual production of the institution. The dissertation also proposes the creation of an Institutional Memory Program to strengthen the preservation and dissemination of ESPM's memory, ensuring the continuity and appreciation of the institution's identity and cultural heritage. In conclusion, ESPM libraries are essential for the preservation of the institution's cultural and intellectual heritage, reinforcing its identity and contributing to the preservation of its memory